The predictive value of serum PAF-AH and Visinin-like protein 1 for poor prognosis in patients with hypertensive intracerebral hemorrhage: Serum PAF-AH and Visinin-like protein 1 in hypertensive intracerebral hemorrhage - Bai, Yaqiang; Wei, Man; Yang, Zhikun; Bu, Fanyan; Wang, Ziyang; Zhu, Binfeng; Zhu, Zuolei (Journal of Medical Biochemistry, 2026)
Objective To determine if serum levels of retinoid protein-like protein 1 (VILIP-1), Platelet-Activating Factor Acetylhydrolase (PAF-AH), and 8-hydroxydeoxyguanosine (8-OHDG) are prognostic of a poor prognosis in patients with hypertensive intracerebral hemorrhage. Methods The 194 patients in the cerebral hemorrhage group were hospitalized for hypertensive cerebral hemorrhage between January 2022 and January 2024. Forty-five healthy individuals who underwent concurrent physical examinations at the hospital were selected to form the healthy control group. To observe the differences in the levels of serum PAF-AH, VILIP-1 and 8-OHDG, the relationship with the amount of intracerebral hemorrhage, the severity of intracerebral hemorrhage and poor prognosis, and how effectively it predicts the bad outcome of patients suffering from hypertensive intracerebral hemorrhage. Results Serum PAF-AH, VILIP-1, and 8-OHDG levels were substantially greater in the brain hemorrhage group than in the healthy control group (P<0.05). The levels of serum PAF-AH, VILIP-1 and 8-OHDG in the cerebral hemorrhage group increased with the increase of the amount of cerebral hemorrhage and the severity of nerve defect, and patients with poor prognoses had significantly greater serum levels of PAF-AH, VILIP-1, and 8-OHDG than patients with excellent prognoses (P<0.05). The levels of serum PAF-AH, VILIP-1 and 8-OHDG have high value in predicting the poor prognosis of patients with cerebral hemorrhage. The combined detection’s area under the curve (AUC) was 0.925, its sensitivity was 95.4%, and its specificity was 71.2%. The AUC of the three indicators found independently did not differ statistically significantly (P>0.05). Conclusion PAF-AH, VILIP-1 and 8-OHDG are involved in the occurrence and development process of hypertensive intracerebral hemorrhage. The increase of their levels is related to poor prognosis. Combined detection is helpful to improve the predictive efficacy of poor prognosis in patients with hypertensive intracerebral hemorrhage.